Comparison of thoracic ultrasonography and thoracic radiography between healthy adult horses and horses with bacterial pneumonia using a novel, objective ultrasonographic scoring system - Hepworth-Warren, Kate L.; Nelson, Nathan; Dembek, Katarzyna A.; Young, Kimberly A. S. (Frontiers in Veterinary Science, 2022)
Background- Thoracic ultrasonography (TUS) is widely used in equine practice but comparison to radiography is limited in horses. Objectives- To validate a novel, objective scoring system for TUS in adult horses and to compare ultrasonographic and radiographic findings. Animals- 13 healthy horses and 9 with confirmed bacterial pneumonia Methods- Prospective study in which TUS and radiography were performed on healthy horses and those with bacterial pneumonia confirmed by clinical signs and results of transtracheal wash analysis. Ultrasonography was scored utilizing a novel scoring system evaluating number of comet tail lesions, the presence or absence of pleural effusion and/or pulmonary consolidation in each intercostal space. Eighteen horses had thoracic radiographs taken that were scored by a board-certified radiologist utilizing a previously described system. Total scores were recorded and compared between control and diseased patients. Results/Findings- Ultrasonographic scores were significantly higher in the diseased group (median= 126) than in the control group (median = 20, p = 0.01). Receiver operating characteristics (ROC) analysis identified a sensitivity of 66.7% (95% CI 0.417 - 1) and specificity of 92.3% (95% CI 0.462 - 1) for the ability of ultrasonography to identify bacterial pneumonia utilizing a TUS score cutoff of 37. Conclusions and Clinical Importance- TUS had moderate sensitivity and high specificity for identification of bacterial pneumonia in adult horses. TUS appears to be an acceptable stand-alone imaging modality for diagnosis of bacterial pneumonia in horses when radiography is not practical.